Early‐life house dust mite allergens, childhood mite sensitization, and respiratory outcomes. Issue 7 (20th April 2015) - Casas, L.; Sunyer, J.; Tischer, C.; Gehring, U.; Wickman, M.; Garcia‐Esteban, R.; Lehmann, I.; Kull, I.; Reich, A.; Lau, S.; Wijga, A.; Antó, J. M.; et al.
Abstract Background Exposure to indoor allergens during early life may play a role in the development of the immune system and inception of asthma. Objective To describe the house dust mite (HDM) allergen concentrations in bedroom dust during early life and to evaluate its associations with HDM sensitization, wheezing, and asthma, from birth to school age, in 5 geographically spread European birth cohorts. Methods We included 4334 children from INMA‐Menorca (Spain), BAMSE (Sweden), LISAplus and MAS (Germany), and PIAMA‐NHS (the Netherlands). Dust samples were collected from bedrooms during early life and analyzed for Dermatophagoides pteronyssinus (Der p1) and Dermatophagoides farinae (Der f1). HDM concentrations were divided into four categories. Sensitization was determined by specific IgE. Wheezing and asthma information up to 8/10 years was collected through questionnaires. We performed mixed‐effects logistic regression models and expressed associations as odds ratios with 95% confidence intervals. Results House dust mite concentrations varied across cohorts. Mean allergen concentrations were highest in INMA‐Menorca (geometric mean (GM) Der p1 = 3.3 μg/g) and LISAplus (GM Der f1 = 2.1 μg/g) and lowest in BAMSE (GM Der p1 = 0.1 μg/g, Der f1 = 0.3 μg/g). Moderate and high HDM concentrations were significantly (P‐values < 0.05) associated with 50–90% higher prevalence of HDM sensitization. No significant associations were observed with respiratory outcomes. Conclusion Our study based on geographically spread regions, a large sample size, and a wide range of allergen concentration shows that HDM allergen concentrations vary across regions and that exposure during early life plays a role in the development of allergic sensitization but not in the development of respiratory outcomes.